The acute effects of strength training on running performance over two consecutive days - Doma, K.; Deakin, G. B. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Strength training (ST) has been shown to impair running economy with an 8-hour recovery period (Palmer et al., 2001). Accordingly, ST may interfere with endurance adaptations by causing acute detrimental effects on endurance training stimuli. However, to determine whether there are cumulative effects of strength training on endurance training stimulus, it is essential to examine the acute effect of strength training on endurance performance over consecutive days. Subsequently, the purpose of this study was to examine the acute effects of strength training on running performance over two consecutive days. Methods: Six male and four female moderately trained runners undertook two running performance tests (RP1 and RP2) 10- and 24 hours following a strength training session, respectively. A baseline running performance test (Base RP) was conducted at least two days before the ST session. Maximal voluntary contractions of the knee extensors were collected prior to and following the ST session and RP1 and RP2. The running performance test was a three stage discontinuous test with the first two stages set at 70- and 90% of ventilatory threshold (VT), respectively, for 10 minutes. The last stage was set at 110% of VT in order to record time-to-exhaustion (TTE). There were two minutes rest between each stage with oxygen cost (CR) and blood lactate (BL) collected during and after the running performance test, respectively. The exercises during the ST session were performed in the order of incline leg press, leg extension and leg curls. All ST exercises were performed at six repetitions maximum with six sets for the incline leg press and four sets for the leg extension and leg curls, respectively, with three minutes rest between each set and exercise. A one way repeated measures analysis of variance was used to determine differences in performance variables. Results: The TTE was significantly less during RP 1 and RP2 compared to Base RP (P < 0.05). In addition, MVC following the ST session and prior to and following RP 1 and RP2 were significantly less than the MVC prior to the ST session (P < 0.05). There were no significant differences in CR and BL between Base RP, RP 1 and RP2.